Migration, international trade and capital formation: Cause or effect? - Gabriel J. Felbermayr; Volker Grossmann; Wilhelm K. Kohler (Institute for the Study of Labor (IZA), 2012)
In this paper, we provide an overview of the relationship between international migration and international trade as well as capital movements. After taking a brief historical perspective, we first investigate migration flows between two countries in a static, neoclassical context. We allow for a disaggregated view of migration that distinguishes between different types of labor and emphasizes the distinction between migration flows and pre-existing stocks. We focus on different welfare channels, on internal income distribution, international income convergence and on whether migration and trade are substitutes or complements. Complementarity/substitutability hinges on whether countries share the same technology, and the pivotal question is whether or not technology is convex. Generally, under substitutability between trade and migration and with convex technology, globalization tends to lead to convergence. Moreover, under non-convex technology trade and migration tend to be complements. Turning to dynamic models with capital adjustment costs and capital mobility, the same is true for the relationship between migration and capital flows. Nevertheless, in neoclassical models, we may observe emigration at the same time as capital accumulates during the transition to a steady state. Moreover, we can explain reverse migration. We also touch upon the effects of migration on the accumulation of both knowledge and human capital, by invoking endogenous growth theory. Finally, we review the empirical literature exploring the link between migration and trade. The discussion is based on the so called gravity model of trade, in which trade between pairs of countries is related to measures of their respective sizes, preferences, and trade costs. We revisit the identification of the overall trade-creating effect of migration and its break-down into the trade channel and the preference channel. We clarify the role of product differentiation for the size of estimated effects, discuss the role of immigrants' education and occupation, and emphasize direct and indirect networks and their trade-enhancing potential.
Keywords: F1; F2; F4; 330; migration; international trade; capital movements; capital formation; globalization; Globalisierung; Entwicklungskonvergenz; Internationale Wanderung; Außenwirtschaft; Kapitalmobilität; Investition; Zwei-Länder-Modell; Theorie; Welt